Reform And Westernization During The Ottoman Empire - Azman, Zainal; Supriadi; Helandri, Joni (El-Ghiroh : Jurnal Studi Keislaman, 2026)
The trajectory of reform and Westernization in the Ottoman Empire reflects a complex and gradual transformation shaped by internal challenges and external pressures. This study examines the dynamics of reform initiatives from the Tanzimat period under Sultan Mahmud II to their culmination in the era of Mustafa Kemal Atatürk. The introduction situates Ottoman reform within the broader context of imperial decline and modernization, emphasizing leadership-driven change as a critical catalyst. Particular attention is given to the Tanzimat era, marked by the promulgation of the Gülhane Edict (1839) and the Hatt-i Hümayun (1856) under Sultan Abdülmecid, which sought to restructure governance, legal systems, and civil rights in line with modern state principles. This research employs a qualitative library-based method, drawing on primary historical documents, classical Ottoman sources, and contemporary scholarly works in Islamic and Middle Eastern studies. Data were analyzed through historical-comparative and interpretative approaches to identify patterns of reform and ideological contestation within Ottoman society. The discussion highlights that Westernization in the Ottoman context generated ideological fragmentation, represented by three dominant currents: Islamism, Westernism, and Nationalism. These competing perspectives shaped both the direction and limitations of reform, demonstrating that modernization in the Ottoman Empire was characterized by negotiation rather than wholesale adoption of Western models. This study concludes that Ottoman reform and Westernization constituted a transformative yet contested process that fundamentally redefined state, society, and identity in the late Islamic empire.